2018
DOI: 10.2478/hppj-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and determination of characteristics of endophytes from rice plants and their role in biocontrol of bacterial blight caused by Xanthomonas oryzae pv. oryzae

Abstract: Summary Endophytic bacteria of rice plants (Oryza sativa L.) from eight diff erent cultivars were screened for their ability in inducing disease symptoms, plant growth promotion and antagonistic activity against Xanthomonas oryzae pv. oryzae. Out of the 63 whole isolates, fi ve were plant pathogens. Based on phenotypic characteristics and 16S rDNA sequence analysis, these were identified as Pseudomonas oryzihabitans, P. fulva, Pantoea ananatis, Pantoea sp., Cellulomonas sp. Four out of the 63 isolates behaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Plant roots, leaves and stems were rst washed in running tap water to remove any soil or contaminant from the eld before being washed in 70% ethanol for 5 minutes. They were transferred to 3% sodium hypochlorite for ve minutes for complete surface sterilization and then rinsed several times in sterile distilled water [27]. The e ciency of surface sterilization was assessed by inoculating 100 µL aliquot of the last rinsing water on Nutrient agar plates and incubating for 48 hours at 28 ±2 ○ C. Absence of any growth indicated complete surface sterilization.…”
Section: Isolation Of Culturable Bacterial Endophytesmentioning
confidence: 99%
“…Plant roots, leaves and stems were rst washed in running tap water to remove any soil or contaminant from the eld before being washed in 70% ethanol for 5 minutes. They were transferred to 3% sodium hypochlorite for ve minutes for complete surface sterilization and then rinsed several times in sterile distilled water [27]. The e ciency of surface sterilization was assessed by inoculating 100 µL aliquot of the last rinsing water on Nutrient agar plates and incubating for 48 hours at 28 ±2 ○ C. Absence of any growth indicated complete surface sterilization.…”
Section: Isolation Of Culturable Bacterial Endophytesmentioning
confidence: 99%
“…Seed treatment with these antagonists caused disease to cease in over 60% of plants. These species have been found as endophytes in rice (Yousefi et al 2018). Endophytic bacteria are able to control the disease caused by bacteria and fungi because they produce hydrolytic enzyme as well as chitinase, protease similar to rhizospheric bacteria B. subtilis from potato rhizosphere (Lestari et al 2017).…”
Section: Suppressing Bacterial Leaf Blight By Ebarrmentioning
confidence: 99%
“…They occupy the same niche inside host plants as that of pathogens and hence can be possibly utilized as good candidates for the management of plant pathogens. Yousefi et al (2018) reported the antagonistic potential of endophytes isolated from rice against BLB. Four endophytes 37.25, 34.25, 33.25 and 28.5% reduction of BLB incidence over control.…”
Section: Introductionmentioning
confidence: 99%